PENGARUH MEDIA POP UP BOOK TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN IPAS KELAS IV SDN 07 PAYARAMAN - Amelia, Safira; Rahman, Andi; Lestari, Hikmah (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to determine the effect of using Pop-Up Book media on students’ learning outcomes in the Natural and Social Sciences (IPAS) subject for fourth-grade students at SDN 07 Payaraman. This research employed a quantitative approach with a One Group Pretest-Posttest Design. The population consisted of all 34 fourth-grade students at SDN 07 Payaraman. Data analysis was conducted using a t-test. The results showed that students’ learning outcomes improved after the use of Pop-Up Book media, with an average posttest score of 79.41. The hypothesis test using an independent sample t-test indicated that tcount=7.524>ttable=1.692 and a significance value of p=0.000<0.05. These results indicate that the alternative hypothesis (Ha) was accepted and the null hypothesis (H0) was rejected. Therefore, it can be concluded that the use of Pop-Up Book media has a significant positive effect on students’ learning outcomes in the IPAS subject for fourth-grade students at SDN 07 Payaraman.